Positive pole piece, preparation method, battery and electric equipment
By preparing lithium nickel oxide positive electrode sheets with suitable active specific surface area and doping metal elements on the surface of the material, the problem of insufficient rate performance and cycle life of lithium-ion batteries is solved, achieving more efficient fast charging and longer battery life.
Patent Information
- Application Number
- CN202410294999.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-14
- Publication Date
- 2025-04-15
AI Technical Summary
The rate performance and cycle life of existing lithium-ion batteries need to be further improved to meet the needs of fast charging and efficient use.
By preparing a positive electrode sheet with an active specific surface area in the range of 2 cm2/g to 4 cm2/g, lithium nickel oxide is used as the positive electrode active material, and metal elements are doped on the surface of the material to improve cyclic stability.
It improves the rate performance of the positive electrode plate and the fast charging capacity of the battery, while extending the battery's cycle life and reducing side reactions and material losses.
Smart Images

Figure CN119833566A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a positive electrode sheet, a preparation method, a battery and an electrical device. Background Art
[0002] With the development of modern science and technology, lithium-ion batteries are considered to be the first choice of green and environmentally friendly batteries because of their high energy density, long cycle life, and good environmental protection. Lithium-ion batteries can be widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as electric vehicles, power tools, military equipment, aerospace and other fields. The cycle performance of lithium batteries needs to be further improved. Summary of the invention
[0003] In view of this, the present application mainly provides a positive electrode sheet, a preparation method, a battery and an electrical device, so as to improve the rate performance of the positive electrode sheet.
[0004] In order to solve the above technical problems, the first technical solution adopted in the present application is: providing a positive electrode plate, the positive electrode plate includes a positive electrode active material, the positive electrode active material includes lithium nickel oxide, and the active specific surface area of the positive electrode plate is greater than or equal to 2cm 2 / g, and less than or equal to 4cm 2 / g.
[0005] In the embodiment of the present application, for the positive electrode sheet formed by the lithium nickel oxide positive electrode active material, the active specific surface area of the positive electrode sheet is controlled within the above range, so that the active specific surface area of the positive electrode sheet is large, which is conducive to the release or embedding of active ions from the positive electrode active material, and is conducive to improving the transmission rate of active ions (lithium ions), and is conducive to improving the rate performance after the positive electrode sheet is assembled into a battery, and improving the fast charging capability of the battery. At the same time, the active specific surface area of the positive electrode sheet is maintained within the above value, which can avoid the aggravation of side reactions and large material losses caused by the excessive activity of the positive electrode active material, thereby improving the life of the battery.
[0006] Among them, the active specific surface area of the positive electrode plate is the electrochemically active specific surface area of the positive electrode plate. The active specific surface area of the positive electrode plate is common knowledge in the art, has a meaning known in the art, and can be measured by methods and instruments in the art.
[0007] In any embodiment, the active specific surface area of the positive electrode sheet is greater than or equal to 2.5 cm 2 / g, and less than or equal to 3.5cm 2 / gIn the embodiment of the present application, the active specific surface area of the positive electrode plate is within the above range, so that the active ions can be easily released from or embedded in the positive electrode active material, which is beneficial to improving the transmission rate of the active ions and improving the rate performance of the positive electrode plate after it is assembled into a battery; at the same time, it can reduce the occurrence of side reactions and improve the cycle performance of the positive electrode plate after it is assembled into a battery.
[0008] In any embodiment, the positive electrode active material includes primary particles, and in the scanning electron microscope image of the positive electrode active material, the half-peak width of the particle size distribution of the primary particles of the positive electrode active material is 1.3μm-2μm. In the embodiment of the present application, the half-peak width of the particle size distribution of the primary particles of the positive electrode active material is within the above range, the concentration of the particle size in the particle size distribution of the primary particles of the positive electrode active material is relatively large, the uniformity of the primary particles is relatively strong, and the uniformity of the paths of active ion embedding and detachment is relatively high, which is conducive to improving the cycle performance and rate performance of the battery assembled from the positive electrode sheet.
[0009] The half-peak width of the particle size distribution of the primary particles of the positive electrode active material is common knowledge in the art, has a meaning known in the art, and can be measured by methods and instruments in the art.
[0010] In any embodiment, the positive electrode active material includes primary particles, and in the scanning electron microscope image of the positive electrode active material, the average particle size of the primary particles is 1.5μm-2.5μm. In the embodiment of the present application, the average particle size of the primary particles of the positive electrode active material is within the above range, so that the particle size of the primary particles of the positive electrode active material is better, so that the specific surface area of the primary particles of the positive electrode active material is better, the positive electrode active material has fewer side reactions in the electrolyte, and the cycle attenuation is smaller; the active ion deintercalation path of the positive electrode active material is better, the kinetics is better, so that the cycle performance and rate performance of the battery assembled with the positive electrode sheet are better.
[0011] The average particle size of the primary particles is common knowledge in the art, has a meaning commonly known in the art, and can be measured by methods and instruments in the art.
[0012] In any embodiment, the average particle size of the primary particles is 1.5 μm-1.99 μm. In the embodiment of the present application, the average particle size of the primary particles of the positive electrode active material is within the above range, so that the particle size of the primary particles of the positive electrode active material is better, so that the specific surface area of the primary particles of the positive electrode active material is better, the positive electrode active material has fewer side reactions in the electrolyte, and the cycle attenuation is smaller; the active ion deintercalation path of the positive electrode active material is better, the kinetics is better, so that the cycle performance and rate performance of the battery assembled with the positive electrode sheet are better.
[0013] In any embodiment, the positive electrode active material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and cobalt-free ternary positive electrode materials. Among them, the cobalt-free ternary positive electrode material includes lithium nickel oxide, or lithium nickel oxide doped with metal elements.
[0014] In any embodiment, the positive electrode active material includes a structural formula of Li a Ni x Co y A z M (1-x-y-z) O2 material, wherein 0.9≤a≤1.1, 0.54≤x≤0.99, 0≤y≤0.2, 0≤z≤0.4; wherein A includes Mn and / or Al, and M includes one or more of V, Co, Mg, Fe, Zr, Y, Nb, Mo, Cr, B, Ti, Nb, and W. In the embodiment of the present application, the positive electrode active material includes lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium nickel oxide material, which can be doped with the above metal elements, which can improve the cycle life of the positive electrode sheet to a certain extent.
[0015] In any embodiment, Li a Ni x Co y A z M (1-x-y-z) In the material of O2, at least part of the M element is doped in the surface layer of the positive electrode active material. In the embodiment of the present application, the M element is mainly distributed in the Li a Ni x Co y A z M (1-x-y-z) The surface layer of the O2 material, specifically, may be mainly located at Li a Ni x Co y A z M (1-x-y-z) The area from the outer surface of the O2 material to a distance of 0.3d is doped with M elements, where d represents Li a Ni x Co y A z M (1-x-y-z) The diameter or particle size of the O2 material. In the embodiment of the present application, at least part of the M element is doped in Li a Ni x Co y A z M (1-x-y-z)The surface layer of the O2 material. During the battery charging and discharging process, the surface layer of the positive electrode active material reacts first, and the active ions are first embedded in or released from the surface layer. By doping the surface layer with metal elements, it is beneficial to greatly improve the cycle stability of the positive electrode active material, while reducing the amount of M element, which can improve the energy density of the positive electrode active material.
[0016] In any embodiment, the positive electrode active material further includes a coating layer, and the coating layer contains one or more of Al, B, Co, Ti, Nb, W, and Zr. a Ni x Co y A z M (1-x-y-z) The coating layer is set on the surface of the O2 material. On the one hand, the coating layer contains the above elements, and the coating layer has good ion conductivity, which is conducive to the embedding and extraction of active ions and can improve the lithium ion transmission efficiency. On the other hand, the coating layer can also inhibit the electrolyte from reacting with Li a Ni x Co y A z M (1-x-y-z) O2 corrosion of the material, while reducing the loss of electrolyte due to side reactions, and improving the cycle stability of the battery. In the present application, by controlling the amount of the coating layer, the positive electrode active material has a higher cycle stability and a higher energy density. In the present application, the M element is doped with Li a Ni x Co y A z M (1-x-y-z) The material of O2 is the surface layer of the inner core, which is located within the coating layer, and the M element is not doped in the coating layer.
[0017] In any embodiment, the positive electrode active material comprises a single crystal. In the embodiment of the present application, the positive electrode active material comprises a single crystal. The single crystal structure of the lithium nickel oxide positive electrode active material is more stable and has less side reactions, which is conducive to improving the cycle stability of the positive electrode sheet.
[0018] In any embodiment, the positive electrode sheet further includes a conductive agent and a binder, and the mass ratio of the positive electrode active material, the conductive agent and the binder is (88-98): (0.5-7): (0.5-5). By controlling the mass ratio of the positive electrode active material, the conductive agent and the binder, the active specific surface area of the positive electrode sheet is within a preferred range, the active sites of the conductive agent are preferred, and the cycle performance of the battery is preferred.
[0019] The second aspect of the present application provides a method for preparing a positive electrode sheet, wherein a slurry containing a positive electrode active material is coated on a current collector, and then dried, cold pressed, and sliced to form a positive electrode sheet, wherein the active specific surface area of the positive electrode sheet is greater than or equal to 2 cm 2 / g, and less than or equal to 4cm 2 / g, the positive electrode active material includes lithium nickel oxide. In the embodiment of the present application, the prepared positive electrode sheet has the same advantages as the positive electrode sheet of the first aspect.
[0020] In any embodiment, the preparation method of the positive electrode active material includes: adding a nickel source to water, adding an alkaline solution, coprecipitating, adjusting the pH reaction to form a positive electrode active material precursor, the volume average particle size DV50 of the positive electrode active material precursor is 2μm-4μm; mixing the lithium source and the positive electrode active material precursor, and annealing to form the positive electrode active material. In the embodiment of the present application, the positive electrode active material precursor is prepared by coprecipitation, and the volume average particle size DV50 of the positive electrode active material precursor is controlled to be 2μm-4μm, so as to control the average particle size of the primary particles of the positive electrode active material formed later to be 1.5μm-2.5μm.
[0021] In any embodiment, the specific surface area of the positive electrode active material precursor is 13 m 2 / g-35m 2 / g. In the embodiment of the present application, by controlling the specific surface area of the positive electrode active material precursor within the above range, the specific surface area of the positive electrode active material precursor is larger, the reaction activity of the positive electrode active material precursor is stronger, and the gradient of the particles of the positive electrode active material formed by the positive electrode active precursor during the later annealing treatment is reduced, so that the uniformity of the primary particles of the positive electrode active material is stronger.
[0022] In any embodiment, the atmosphere of the annealing treatment contains oxygen, and the volume percentage of oxygen accounts for more than 50% of the atmosphere. In the embodiment of the present application, the atmosphere of the annealing treatment contains oxygen, so that the reaction activity of the positive electrode active material precursor is large and the reaction is more sufficient.
[0023] In any embodiment, the atmosphere of the annealing treatment contains oxygen, and the volume percentage of oxygen accounts for more than 80% of the atmosphere. In the embodiment of the present application, the atmosphere of the annealing treatment contains oxygen, and the content of oxygen in the annealing atmosphere is controlled to be more than 80%, so that the reaction activity of the positive electrode active material precursor is greater, the reaction is more sufficient, and the occurrence of a situation in which the proportion of small particles in the formed positive electrode active material is high is reduced, so that the particles of the positive electrode active material are around 1.5μm-2.5μm, and the half-peak width of the particle size distribution is in the range of 1.3μm-2μm, so that the particle distribution of the positive electrode active material is more concentrated.
[0024] In any embodiment, adjusting the pH reaction to form a positive electrode active material precursor includes: adjusting the pH, stirring the reaction, and forming a positive electrode active material precursor; wherein the stirring rate is 600rpm-1000rpm. In the embodiment of the present application, by controlling the stirring speed, the volume average particle size DV50 of the positive electrode active material precursor is controlled, thereby controlling the half-peak width of the particle size distribution of the primary particles of the positive electrode active material, and controlling the particle size of the primary particles.
[0025] In any embodiment, a lithium source and a positive electrode active material precursor are mixed and annealed to form a positive electrode active material, including: mixing a lithium source, a positive electrode active material precursor and an M source, performing a first annealing treatment in an atmosphere containing oxygen, and crushing to obtain a first positive electrode active material, wherein the M source includes a compound containing one or more of the elements Al, B, Co, Ti, Nb, W, and Zr. In an embodiment of the present application, a lithium nickel oxide positive electrode active material doped with the M element is formed by mixing a positive electrode active material precursor with an M source and performing an annealing treatment. In an embodiment of the present application, by crushing after annealing, the particle size of the formed positive electrode active material can be reduced and the agglomeration of the positive electrode active material can be reduced. In an embodiment of the present application, the first positive electrode active material formed is a positive electrode active material.
[0026] In any embodiment, the lithium source, the positive electrode active material precursor and the M source are mixed, and the first annealing treatment is performed in an atmosphere containing oxygen, and the first positive electrode active material is obtained by crushing, and the first positive electrode active material is obtained, and the first positive electrode active material is mixed with the coating source, and the second annealing treatment is performed to form a second positive electrode active material, and the coating source includes a compound containing one or more of the elements Al, B, Co, Ti, Nb, W, and Zr. In the embodiment of the present application, the second positive electrode active material obtained by mixing the first positive electrode active material with the coating source and performing an annealing treatment is the positive electrode active material, and the coating source can be coated on the surface of the first positive electrode active material, thereby improving the lithium ion transmission efficiency of the positive electrode active material and improving the cycle stability of the positive electrode active material.
[0027] In any embodiment, the temperature of the first annealing treatment is 700° C.-1100° C. In the embodiment of the present application, by controlling the temperature of the first annealing treatment within the above range, the primary particles of the formed positive electrode active material have greater uniformity.
[0028] In any embodiment, the temperature of the second annealing treatment is 350° C.-600° C. By controlling the temperature of the second annealing treatment, a relatively uniform coating layer is formed.
[0029] In any embodiment, the crushing includes crushing in a jet mill with a classifying wheel frequency of 40 Hz-60 Hz. In the embodiment of the present application, the higher the frequency of the classifying wheel, the smaller the particles are crushed and the wider the particle size distribution. By controlling the frequency of the classifying wheel within the above range, it is convenient to reduce agglomeration, control the half-peak width of the particle size distribution of the primary particles to 1.3 μm-2 μm, and control the active specific surface area of the positive electrode sheet to 2.5 cm 2 / g-4cm 2 / g.
[0030] The third aspect of the present application provides a battery, including a positive electrode sheet including the positive electrode sheet of the first aspect, or / and a positive electrode sheet prepared by the method of the second aspect. The embodiments of the present application have at least the same advantages as the positive electrode sheet of the first aspect, or / and the same advantages as the positive electrode sheet prepared by the preparation method of the second aspect.
[0031] The fourth aspect of the present application includes an electrical device, including the battery of the third aspect. The embodiments of the present application have at least the same advantages as the battery of the third aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic structural diagram of a vehicle according to one embodiment of the present application.
[0033] Figure 2 It is a schematic diagram of the exploded structure of a battery according to one embodiment of the present application.
[0034] Figure 3 It is a schematic diagram of the exploded structure of a battery cell according to one embodiment of the present application.
[0035] Figure 4 1 is a scanning electron microscope image of a positive electrode active material according to an embodiment of the present application.
[0036] Figure 5a This is a particle contour diagram of a scanning electron microscope image of a positive electrode active material according to one embodiment of the present application after automatic artificial intelligence identification.
[0037] Figure 5b Graph 1 is a normal distribution diagram of the particle sizes of primary particles of the positive electrode active material according to one embodiment of the present application. DETAILED DESCRIPTION
[0038] Below, the battery cells, batteries and electrical equipment of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0039] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0040] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0041] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0042] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0043] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, "include" and "comprising" may represent that other components not listed may also be included or only listed components may be included or only listed components may be included.
[0044] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0045] Unless otherwise specified, in this application, the unit of temperature is Celsius (°C).
[0046] As a new type of green secondary battery, lithium-ion batteries are widely used in electric vehicles, energy storage systems and renewable energy fields. With the new development of lithium-ion batteries in my country, lithium-ion batteries will surely achieve many improvements. Fast charging capability is an important goal of power battery development.
[0047] The present application provides a positive electrode sheet, the positive electrode sheet includes a positive electrode active material, the positive electrode active material includes lithium nickel oxide, and the active specific surface area of the positive electrode sheet is greater than or equal to 2 cm 2 / g, and less than or equal to 4cm 2 / g. Among them, the active specific surface area of the positive electrode sheet can be 2cm 2 / g, 2.5cm 2 / g, 2.8cm 2 / g, 3cm 2 / g, 3.5cm 2 / g, 4cm 2 / g, etc. Or a range of any two of the above values, such as 2cm 2 / g-2.8cm 2 / g, 2.8cm 2 / g-3.5cm 2 / g, 3.5cm 2 / g-4cm 2 / g, etc.
[0048] In the embodiment of the present application, for the positive electrode sheet formed by the lithium nickel oxide positive electrode active material, the active specific surface area of the positive electrode sheet is controlled within the above range, so that the active specific surface area of the positive electrode sheet is larger, which is conducive to the release or embedding of active ions from the positive electrode active material, and is conducive to improving the transmission rate of active ions (lithium ions), and is conducive to improving the rate performance after the positive electrode sheet is assembled into a battery, and improving the fast charging capability of the battery. At the same time, the active specific surface area of the positive electrode sheet is maintained within the above value, which can avoid the aggravation of side reactions and large material losses caused by the excessive activity of the positive electrode active material, thereby improving the life of the battery.
[0049] In some embodiments, the active specific surface area of the positive electrode sheet is greater than or equal to 2.5 cm 2 / g, and less than or equal to 3.5cm 2 / g. In the embodiment of the present application, the active specific surface area of the positive electrode sheet is within the above range, so that the active ions can be easily released or embedded from the positive electrode active material, which is beneficial to improve the transmission rate of the active ions and the rate performance of the positive electrode sheet after being assembled into a battery; at the same time, it can reduce the occurrence of side reactions and improve the cycle performance of the positive electrode sheet after being assembled into a battery. Among them, the active specific surface area of the positive electrode sheet can be 2.5cm 2 / g, 2.8cm 2 / g, 3cm 2 / g, 3.5cm 2 / g, etc. Or a range of any two of the above values, such as 2.5cm 2 / g-2.8cm 2 / g, 2.8cm 2 / g-3cm 2 / g, 3cm 2 / g-3.5cm 2 / g, etc.
[0050] In some embodiments, the positive electrode active material includes primary particles, and in the scanning electron microscope image of the positive electrode active material, the half-peak width of the particle size distribution of the primary particles of the positive electrode active material is 1.3μm-2μm. In the embodiment of the present application, the half-peak width of the particle size distribution of the primary particles of the positive electrode active material is within the above range, the concentration of the particle size in the particle size distribution of the primary particles of the positive electrode active material is relatively large, the uniformity of the primary particles is relatively strong, and the path uniformity of the active ion embedding and detachment is relatively high, which is conducive to improving the cycle performance and rate performance of the positive electrode sheet assembled into a battery. Among them, the half-peak width of the particle size distribution of the primary particles of the positive electrode active material can be 1.3μm, 1.5μm, 1.7μm, 1.8μm, 1.9μm or 2μm, etc., or a range value composed of any two of the above values, such as 1.3μm-1.7μm, 1.7μm-1.9μm, 1.9μm-2μm, etc.
[0051] In some embodiments, the positive electrode active material includes primary particles, and in the scanning electron microscope image of the positive electrode active material, the average particle size of the primary particles is 1.5μm-2.5μm. In the embodiment of the present application, the average particle size of the primary particles of the positive electrode active material is within the above range, so that the particle size of the primary particles of the positive electrode active material is better, so that the specific surface area of the primary particles of the positive electrode active material is better, the positive electrode active material has fewer side reactions in the electrolyte, and the cycle attenuation is smaller; the active ion deintercalation path of the positive electrode active material is better, the kinetics is better, so that the cycle performance and rate performance of the positive electrode sheet assembled into a battery are better. Among them, the average particle size of the primary particles can be 1.5μm, 1.7μm, 1.8μm, 2μm, 2.2μm or 2.5μm, etc., or a range value composed of any two of the above values, such as 1.5μm-1.8μm, 1.8μm-2μm, 2μm-2.5μm, etc.
[0052] In some embodiments, the average particle size of the primary particles is 1.5μm-1.99μm. In the embodiment of the present application, the average particle size of the primary particles of the positive electrode active material is within the above range, so that the particle size of the primary particles of the positive electrode active material is better, so that the specific surface area of the primary particles of the positive electrode active material is better, the positive electrode active material has fewer side reactions in the electrolyte, and the cycle attenuation is smaller; the active ion deintercalation path of the positive electrode active material is better, the kinetics is better, so that the cycle performance and rate performance of the positive electrode sheet assembled into a battery are better. Among them, the average particle size of the primary particles can be 1.5μm, 1.7μm, 1.8μm, 1.9μm or 1.99μm, etc., or a range value composed of any two of the above values, such as 1.5μm-1.7μm, 1.7μm-1.8μm, 1.8μm-1.99μm, etc.
[0053] In some embodiments, the positive electrode active material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and cobalt-free ternary positive electrode materials. Among them, the cobalt-free ternary positive electrode material includes lithium nickel oxide, or lithium nickel oxide doped with metal elements.
[0054] In some embodiments, the positive electrode active material includes a structural formula of Li a Ni x Co y A z M (1-x-y-z)O2 material, wherein 0.9≤a≤1.1, 0.54≤x≤0.99, 0≤y≤0.2, 0≤z≤0.4; wherein A includes Mn and / or Al, and M includes one or more of V, Co, Mg, Fe, Zr, Y, Nb, Mo, Cr, B, Ti, Nb, and W. In the embodiment of the present application, the positive electrode active material includes lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium nickel oxide material, which can be doped with the above metal elements, which can improve the cycle life of the positive electrode sheet to a certain extent.
[0055] In some embodiments, Li a Ni x Co y A z M (1-x-y-z) In the material of O2, at least part of the M element is doped in the surface layer of the positive electrode active material. In the embodiment of the present application, the M element is mainly distributed in the Li a Ni x Co y A z M (1-x-y-z) The surface layer of the O2 material, specifically, may be located at Li a Ni x Co y A z M (1-x-y-z) The area from the outer surface of the O2 material to a distance of 0.3d is doped with M elements, where d represents Li a Ni x Co y A z M (1-x-y-z) The diameter or particle size of the O2 material. In the embodiment of the present application, at least part of the M element is doped in Li a Ni x Co y A z M (1-x-y-z) The surface layer of the O2 material. During the battery charging and discharging process, the surface layer of the positive electrode active material reacts first, and the active ions are first embedded in or released from the surface layer. By doping the surface layer with metal elements, it is beneficial to greatly improve the cycle stability of the positive electrode active material, while reducing the amount of M element, which can improve the energy density of the positive electrode active material.
[0056] In some embodiments, the positive electrode active material further includes a coating layer, which contains one or more of the elements Al, B, Co, Ti, Nb, W, and Zr. Based on the mass of the positive electrode active material, the mass fraction of the coating layer is greater than zero and less than or equal to 5%. In the embodiment of the present application, by a Ni x Co y Az M (1-x-y-z) The coating layer is set on the surface of the O2 material. On the one hand, the coating layer contains the above elements, and the coating layer has good ion conductivity, which is conducive to the embedding and extraction of active ions and can improve the lithium ion transmission efficiency. On the other hand, the coating layer can also inhibit the electrolyte from reacting with Li a Ni x Co y A z M (1-x-y-z) The corrosion of O2 materials is reduced, and the loss of electrolyte caused by side reactions is reduced, thereby improving the cycle stability of the battery. In the present application, by controlling the amount of the coating layer, the positive electrode active material has a higher cycle stability and a higher energy density.
[0057] In some embodiments, the positive electrode active material comprises a single crystal. In the embodiment of the present application, the positive electrode active material comprises a single crystal. The lithium nickel oxide positive electrode active material with a single crystal structure has strong stability and small side reactions, which is conducive to improving the cycle stability of the positive electrode sheet.
[0058] In some embodiments, the positive electrode sheet further includes a conductive agent and a binder, and the mass ratio of the positive electrode active material, the conductive agent and the binder is (88-98): (0.5-7): (0.5-5). By controlling the mass ratio of the positive electrode active material, the conductive agent and the binder, the active specific surface area of the positive electrode sheet is within a preferred range, the active sites of the conductive agent are preferred, and the cycle performance of the battery is preferred. Among them, the mass ratio of the positive electrode active material, the conductive agent and the binder is 88:0.5:0.5, 90:0.5:0.5, 95:0.5:0.5, 98:0.5:0.5, 88:1:0.5, 88:3:0.5, 88:5:0.5, 88:7:0.5, 92:1:0.5, 92:1:1, 92:1:3, 92:1:5, 95:3:3, 98:7:5, etc., or a range value composed of any two of the above values, for example, (88-92):(0.5-1):(0.5-1), (92-95):(1-3):(1-3), (95-98):(3-7):(3-5), etc.
[0059] The second aspect of the present application provides a method for preparing a positive electrode sheet, wherein a slurry containing a positive electrode active material is coated on a current collector, and then dried, cold pressed, and sliced to form a positive electrode sheet, wherein the active specific surface area of the positive electrode sheet is greater than or equal to 2 cm 2 / g, and less than or equal to 4cm 2 / g, the positive electrode active material includes lithium nickel oxide. In the embodiment of the present application, the prepared positive electrode sheet has the same advantages as the positive electrode sheet of the first aspect.
[0060] In some embodiments, the preparation of the positive electrode active material includes: adding a nickel source to water, adding an alkaline solution, coprecipitating, adjusting the pH reaction to form a positive electrode active material precursor, and the volume average particle size DV50 of the positive electrode active material precursor is 2μm-4μm; mixing the lithium source and the positive electrode active material precursor, and annealing to form the positive electrode active material. In the embodiment of the present application, the positive electrode active material precursor is prepared by coprecipitation, and the volume average particle size DV50 of the positive electrode active material precursor is controlled to be 2μm-4μm, so as to control the average particle size of the primary particles of the positive electrode active material formed later to be 1.5μm-2.5μm. Specifically, in one embodiment of the present application, the nickel source is added to deionized water to prepare a mixed solution, ammonia water and sodium hydroxide aqueous solution are introduced into the mixed solution, coprecipitated, the pH value of the reaction system is adjusted, and in an inert atmosphere such as nitrogen, stirred, reacted, and the solid phase product after the reaction is washed with deionized water and dried to obtain a positive electrode active material precursor. The embodiments of the present application do not limit the specific type of the alkaline solution.
[0061] In one embodiment of the present application, when a lithium nickel cobalt manganese oxide material is to be prepared, a nickel source, a cobalt source and a manganese source are added to water, and an alkaline solution is added, coprecipitated, the pH is adjusted, and a nickel cobalt manganese precursor is formed by reaction. In other embodiments, when a lithium nickel cobalt aluminum oxide material is to be prepared, a nickel source, a cobalt source and an aluminum source are added to water, and an alkaline solution is added, coprecipitated, the pH is adjusted, and a nickel cobalt aluminum precursor is formed by reaction. Or when a cobalt-free ternary material such as a lithium nickel manganese oxide material is to be prepared, a nickel source and a manganese source are added to water, and an alkaline solution is added, coprecipitated, the pH is adjusted, and a nickel manganese precursor is formed by reaction.
[0062] In some embodiments, the specific surface area of the positive electrode active material precursor is 13 m 2 / g-35m 2 / g. In the embodiment of the present application, by controlling the specific surface area of the positive electrode active material precursor within the above range, the specific surface area of the positive electrode active material precursor is larger, the reaction activity of the positive electrode active material precursor is stronger, and the gradient of the particles of the positive electrode active material formed by the positive electrode active precursor during the later annealing process is reduced, so that the uniformity of the primary particles of the positive electrode active material is stronger. Among them, the specific surface area of the positive electrode active material precursor can be 13m 2 / g, 15m 2 / g, 18m 2 / g, 20m 2 / g, 25m 2 / g, 28m 2 / g, 30m 2 / g, 35m 2 / g, etc., or a range of values consisting of any two of the above values, such as 13m2 / g-20m 2 / g, 20m 2 / g-28m 2 / g, 28m 2 / g-35m 2 / g, etc.
[0063] In some embodiments, the atmosphere of the annealing treatment contains oxygen, and the volume percentage of oxygen in the atmosphere is more than 50%. In the embodiment of the present application, the atmosphere of the annealing treatment contains oxygen, so that the reaction activity of the positive electrode active material precursor is large and the reaction is more sufficient. Among them, the volume percentage of oxygen in the atmosphere is 50%, 60%, 70%, 80%, 90%, 95%, 100%, etc., or a range value composed of any two of the above values, such as 50%-70%, 70%-90%, 90%-100%.
[0064] In some embodiments, the atmosphere of the annealing treatment contains oxygen, and the volume percentage of oxygen accounts for more than 80% of the atmosphere. In the embodiment of the present application, the atmosphere of the annealing treatment contains oxygen, and the content of oxygen in the annealing atmosphere is controlled to be more than 80%, so that the reaction activity of the positive electrode active material precursor is greater, the reaction is more sufficient, and the occurrence of a high proportion of small particles in the formed positive electrode active material is reduced, so that the particles of the positive electrode active material are around 1.5μm-2.5μm, and the half-peak width of the particle size distribution is in the range of 1.3μm-2μm, so that the particle distribution of the positive electrode active material is more concentrated. Among them, the volume percentage of oxygen in the atmosphere is 80%, 90%, 95%, 100%, etc., or a range value composed of any two of the above values, such as 80%-90%, 90%-95%, 95%-100%.
[0065] In some embodiments, adjusting the pH reaction to form a positive electrode active material precursor includes: adjusting the pH, stirring the reaction, and forming a positive electrode active material precursor; wherein the stirring rate is 600rpm-1000rpm. In the embodiment of the present application, the stirring speed is controlled to control the size of the volume average particle size DV50 of the positive electrode active material precursor, thereby controlling the half-peak width of the particle size distribution of the primary particles of the positive electrode active material, and controlling the particle size of the primary particles. The stirring rate can be 600rpm, 700rpm, 800rpm, 860rpm, 900rpm, 1000rpm, etc., or a range value composed of any two of the above values, such as 600rpm-700rpm, 700rpm-860rpm, 860rpm-1000rpm, etc.
[0066] In some embodiments, a lithium source and a positive electrode active material precursor are mixed and annealed to form a positive electrode active material, including: mixing a lithium source, a positive electrode active material precursor and an M source, performing a first annealing treatment in an atmosphere containing oxygen, and crushing to obtain a first positive electrode active material, wherein the M source includes a compound containing one or more of the elements Al, B, Co, Ti, Nb, W, and Zr. In an embodiment of the present application, a lithium nickel oxide positive electrode active material doped with the M element is formed by mixing a lithium source, a positive electrode active material precursor and an M source, and performing an annealing treatment. In an embodiment of the present application, by crushing after annealing, the particle size of the formed positive electrode active material can be reduced, and the agglomeration of the positive electrode active material can be reduced. In an embodiment of the present application, the first positive electrode active material formed is a positive electrode active material.
[0067] In some embodiments of the present application, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate and lithium nitrate.
[0068] In some embodiments of the present application, the M source may be one or more of oxides, carbonates, nitrates, chlorides and hydroxides.
[0069] In some embodiments, the lithium source, the positive electrode active material precursor and the M source are mixed, and the first annealing treatment is performed in an atmosphere containing oxygen, and the first positive electrode active material is obtained by crushing, and the first positive electrode active material is obtained, and the first positive electrode active material is mixed with the coating source, and the second annealing treatment is performed to form a second positive electrode active material, and the coating source includes a compound containing one or more of the elements Al, B, Co, Ti, Nb, W, and Zr. In the embodiment of the present application, the second positive electrode active material obtained by mixing the first positive electrode active material with the coating source and performing an annealing treatment is the positive electrode active material, and the coating source can be coated on the surface of the first positive electrode active material, thereby improving the lithium ion transmission efficiency of the positive electrode active material and improving the cycle stability of the positive electrode active material.
[0070] In some embodiments of the present application, the coating source includes one or more of oxides, carbonates, nitrates, chlorides and hydroxides.
[0071] In some embodiments, the temperature of the first annealing treatment is 700°C-1100°C. In the embodiment of the present application, by controlling the temperature of the first annealing treatment within the above range, the uniformity of the primary particles of the formed positive electrode active material is strong. Among them, the temperature of the first annealing treatment is 700°C, 800°C, 900°C, 950°C, 1000°C, 1100°C, etc., or a range value composed of any two of the above values, 700°C-800°C, 700°C-950°C, 950°C-1100°C, etc.
[0072] In some embodiments, the temperature of the second annealing treatment is 350°C-600°C. By controlling the temperature of the second annealing treatment, a relatively uniform coating layer is formed. The temperature of the second annealing treatment is 350°C, 400°C, 500°C, 550°C, 580°C, 600°C, etc., or a range of any two of the above values, 350°C-500°C, 500°C-580°C, 580°C-600°C, etc.
[0073] In some embodiments, the crushing includes crushing in an air flow mill with a classifying wheel frequency of 40 Hz-60 Hz. In the embodiment of the present application, the higher the frequency of the classifying wheel, the smaller the particles are crushed and the wider the particle size distribution. By controlling the frequency of the classifying wheel within the above range, it is convenient to reduce agglomeration, control the half-peak width of the particle size distribution of the primary particles to 1.3 μm-2 μm, and control the active specific surface area of the positive electrode sheet to 2.5 cm 2 / g-3.5cm 2 / g. The frequency of the grading wheel may be 40 Hz, 45 Hz, 50 Hz, 53 Hz, 60 Hz, etc., or a range of any two of the above values, such as 40 Hz-45 Hz, 45 Hz-53 Hz, 53 Hz-60 Hz, etc.
[0074] The third aspect of the present application provides a battery, including a positive electrode sheet including the positive electrode sheet of the first aspect, or / and a positive electrode sheet prepared by the method of the second aspect. The embodiments of the present application have at least the same advantages as the positive electrode sheet of the first aspect, or / and the same advantages as the positive electrode sheet prepared by the preparation method of the second aspect.
[0075] The fourth aspect of the present application includes an electrical device, including the battery of the third aspect. The embodiments of the present application have at least the same advantages as the battery of the third aspect.
[0076] The battery disclosed in the embodiments of the present application can be used in electrical equipment that uses the battery as a power source or various energy storage systems that use the battery as an energy storage element. Electrical equipment can be, but is not limited to, mobile phones, tablets, laptops, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, etc. Among them, electric toys can include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys, and electric airplane toys, etc., and spacecraft can include airplanes, rockets, space shuttles, and spacecraft, etc.
[0077] For the convenience of description, the following embodiments are described by taking a vehicle 1000 as an example of an electrical device in an embodiment of the present application.
[0078] Please refer to Figure 1 , Figure 1A schematic diagram of the structure of a vehicle 1000 provided for some embodiments of the present application. The vehicle 1000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A battery 100 is provided inside the vehicle 1000, and the battery 100 may be provided at the bottom, head or tail of the vehicle 1000. The battery 100 may be used to power the vehicle 1000, for example, the battery 100 may be used as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 200 and a motor 300, and the controller 200 is used to control the battery 100 to power the motor 300, for example, for starting, navigating and driving the vehicle 1000.
[0079] In some embodiments of the present application, the battery 100 can not only serve as an operating power source for the vehicle 1000, but also serve as a driving power source for the vehicle 1000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000.
[0080] Please refer to Figure 2 , Figure 2 Schematic diagram of the exploded structure of the battery 100 provided for some embodiments of the present application. The battery 100 includes a box 10 and a battery cell 20, and the battery cell 20 is contained in the box 10. Among them, the box 10 is used to provide a storage space for the battery cell 20, and the box 10 can adopt a variety of structures. In some embodiments, the box 10 may include a first part 11 and a second part 12, the first part 11 and the second part 12 cover each other, and the first part 11 and the second part 12 jointly define a storage space for accommodating the battery cell 20. The second part 12 can be a hollow structure with one end open, the first part 11 can be a plate-like structure, and the first part 11 covers the open side of the second part 12, so that the first part 11 and the second part 12 jointly define a storage space; the first part 11 and the second part 12 can also be hollow structures with one side open, and the open side of the first part 11 covers the open side of the second part 12. Of course, the box 10 formed by the first part 11 and the second part 12 can be in a variety of shapes, such as a cylinder, a cuboid, etc.
[0081] In the battery 100, there may be multiple battery cells 20, and the multiple battery cells 20 may be connected in series, in parallel, or in a mixed connection. A mixed connection means that the multiple battery cells 20 are both connected in series and in parallel. The multiple battery cells 20 may be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple battery cells 20 is accommodated in the box 10; of course, the battery 100 may also be a battery module formed by connecting multiple battery cells 20 in series, in parallel, or in a mixed connection, and then the multiple battery modules are connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the box 10. The battery 100 may also include other structures, for example, the battery 100 may also include a busbar component for realizing electrical connection between the multiple battery cells 20.
[0082] Each battery cell 20 may be a battery or a primary battery, or a lithium-sulfur battery, a sodium-ion battery, or a magnesium-ion battery, but is not limited thereto. The battery cell 20 may be cylindrical, flat, rectangular, or in other shapes.
[0083] Please refer to Figure 3 , Figure 3 The schematic diagram of the exploded structure of the battery cell 20 provided in some embodiments of the present application. The battery cell 20 refers to the smallest unit that constitutes the battery. Figure 3 The battery cell 20 includes an end cover 21, a shell 22, a battery cell assembly 23 and other functional components.
[0084] The end cap 21 refers to a component that covers the opening of the shell 22 to isolate the internal environment of the battery cell 20 from the external environment. Without limitation, the shape of the end cap 21 can be adapted to the shape of the shell 22 to match the shell 22. Optionally, the end cap 21 can be made of a material with a certain hardness and strength (such as aluminum alloy), so that the end cap 21 is not easily deformed when squeezed and collided, so that the battery cell 20 can have a higher structural strength and the safety performance can also be improved. Functional components such as electrode terminals 21a can be provided on the end cap 21. The electrode terminal 21a can be used to electrically connect to the battery cell assembly 23 for outputting or inputting electrical energy of the battery cell 20. In some embodiments, the end cap 21 can also be provided with a pressure relief mechanism for releasing the internal pressure when the internal pressure or temperature of the battery cell 20 reaches a threshold. The material of the end cap 21 can also be a variety of materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiments of the present application do not impose special restrictions on this. In some embodiments, an insulating member may be provided inside the end cap 21, and the insulating member may be used to isolate the electrical connection components in the housing 22 from the end cap 21 to reduce the risk of short circuit. For example, the insulating member may be plastic, rubber, or the like.
[0085] The shell 22 is a component used to cooperate with the end cover 21 to form the internal environment of the battery cell 20, wherein the formed internal environment can be used to accommodate the battery cell assembly 23, electrolyte and other components. The shell 22 and the end cover 21 can be independent components, and an opening can be set on the shell 22, and the internal environment of the battery cell 20 is formed by covering the opening with the end cover 21 at the opening. Without limitation, the end cover 21 and the shell 22 can also be integrated. Specifically, the end cover 21 and the shell 22 can form a common connection surface before other components are put into the shell, and when the interior of the shell 22 needs to be encapsulated, the end cover 21 covers the shell 22. The shell 22 can be of various shapes and sizes, such as a rectangular parallelepiped, a cylindrical shape, a hexagonal prism, etc. Specifically, the shape of the shell 22 can be determined according to the specific shape and size of the battery cell assembly 23. The material of the shell 22 can be various, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiment of the present application does not impose any special restrictions on this.
[0086] The cell assembly 23 is a component in the battery cell 100 where electrochemical reactions occur. One or more cell assemblies 23 may be contained in the housing 22. The cell assembly 23 is mainly formed by winding or stacking the positive electrode sheet and the negative electrode sheet, and a separator is usually provided between the positive electrode sheet and the negative electrode sheet. The parts of the positive electrode sheet and the negative electrode sheet with active materials constitute the main body of the cell assembly, and the parts of the positive electrode sheet and the negative electrode sheet without active materials each constitute a tab 23a. The positive tab and the negative tab may be located together at one end of the main body or respectively at both ends of the main body. During the charge and discharge process of the battery, the positive active material and the negative active material react with the electrolyte, and the tab 23a connects the electrode terminals to form a current loop.
[0087] Typically, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0088] [Positive electrode]
[0089] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector.
[0090] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0091] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0092] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0093] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0094] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0095] [Negative electrode]
[0096] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0097] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0098] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0099] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0100] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0101] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0102] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0103] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0104] [Isolation film]
[0105] In some embodiments, the battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0106] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0107] [Electrolytes]
[0108] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0109] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0110] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0111] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0112] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be made into a battery cell assembly by a winding process or a lamination process.
[0113] In some embodiments, the housing 22 may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc.
[0114] The present application has no particular limitation on the shape of the battery cell 20 , which may be cylindrical, square, or any other shape.
[0115] The beneficial effects of the present application are further illustrated below in conjunction with embodiments.
[0116] In order to make the technical problems, technical solutions and beneficial effects solved by the embodiments of the present application clearer, the following will be further described in detail with reference to the embodiments and the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0117] 1. Battery device preparation
[0118] Example 1
[0119]
Preparation of positive electrode
[0120] Step 1) 17.68 kg of nickel sulfate hexahydrate, 4.90 kg of manganese sulfate monohydrate and 2.04 kg of cobalt sulfate heptahydrate were added to deionized water to prepare a mixed solution, wherein the molar ratio of nickel element, cobalt element and manganese element is Ni:Co:Mn=65:7:28; ammonia water (concentration of 0.4 mol / L) and sodium hydroxide aqueous solution (concentration of 1 mol / L) were introduced into the mixed solution, the pH of the reaction system was adjusted to 11.3, and the reaction was carried out under stirring conditions of 40° C. and 600 rpm. During the reaction, inert gas nitrogen was introduced for protection. After the reaction was completed, the solid phase product was washed with deionized water, and after washing, it was dried at 100° C. to obtain a positive electrode active material precursor Ni 0.65 Co 0.07 Mn 0.28 (OH)2.
[0121] Step 2) Mix lithium hydroxide, positive electrode active material precursor and zirconium oxide ZrO2, and then perform mechanical mixing to obtain a mixed material. The amount of lithium hydroxide and positive electrode active material precursor added is such that the ratio of the molar amount of lithium element to the total molar amount of nickel element, cobalt element and manganese element is Li:Me=1.1:1, Me=Ni+Co+Mn; the amount of zirconium oxide added is such that the ratio of the molar amount of zirconium element in the active material particles to the total molar amount of nickel element, cobalt element and manganese element is Zr:Me=0.002:0.998.
[0122] Step 3) The mixed material is placed in a tubular furnace, and the temperature is raised to 940° C. at a rate of 5° C. / min for sintering for 13 h, with an oxygen content of 90%. The mixed material is then cooled to room temperature and crushed to obtain a first positive electrode active material.
[0123] Step 4) The first positive electrode active material and titanium dioxide are mixed in a mass ratio of 100:0.2, and annealed at a temperature of 550°C for 5 hours. The mixture is crushed and sieved by a jet mill at a classifying wheel frequency of 50 Hz to obtain a second positive electrode active material as the final positive electrode active material. The weight of the coating layer is 0.2% of the weight of the first positive electrode active material. The scanning electron microscope image of the final positive electrode active material is shown in FIG. Figure 4 As shown, the particles are evenly distributed and no obvious agglomeration exists.
[0124] Step 5) Prepare a slurry according to the formula of positive electrode active material, conductive agent super-P, carbon nanotubes (CNT), and PVDF with a mass ratio of 96:1.5:0.5:2 in step 4), apply it on a 13μm Al foil, and obtain a positive electrode sheet after vacuum drying at 120°C, cold pressing, and cutting into strips.
[0125]
Preparation of negative electrode sheet
[0126] The negative electrode active material artificial graphite, the conductive agent conductive carbon black, the binder styrene-butadiene rubber and the thickener sodium carboxymethyl cellulose are fully mixed in a mass ratio of 95:1:2:2, and then deionized water is added for stirring and dispersion to obtain a negative electrode slurry. The negative electrode slurry is evenly coated on a copper foil, placed in a drying oven at 80°C for drying, and cold pressed and cut to obtain a negative electrode sheet.
[0127]
Preparation of electrolyte
[0128] In an argon atmosphere glove box, ethylene carbonate (EC) / ethyl methyl carbonate (EMC) were mixed at a volume ratio of 3 / 7 to obtain a solvent, LiPF6 was added at a mass percentage of 12.5% and dissolved in the above solvent, and stirred evenly to obtain an electrolyte.
[0129]
Diaphragm
[0130] Polypropylene film is used as the isolation film.
[0131]
Battery preparation
[0132] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrodes to play a role of isolation, and then wound to obtain a bare cell. The bare cell is placed in an outer package, injected with a prepared electrolyte, and packaged, injected, formed, and vented to obtain a lithium-ion battery.
[0133] Example 12
[0134] The difference from Example 1 is that in the preparation of the positive electrode sheet, zirconium oxide ZrO2 is not added in step 2). The rest is the same as Example 1 and will not be repeated here.
[0135] Embodiment 13
[0136] The difference from Example 1 is that in the preparation of the positive electrode sheet, titanium dioxide is not added in step 4). The rest is the same as Example 1 and will not be repeated here.
[0137] Examples 2-12, Examples 14-18
[0138] Specific process parameters and performance parameters are detailed in Table 1 and Table 2. Other parameters are the same as those in Example 1 and will not be described in detail here.
[0139] Comparative Example 1, Comparative Example 3 and Comparative Example 4
[0140] Specific process parameters and performance parameters are detailed in Table 1 and Table 2. Other parameters are the same as those in Example 1 and will not be described in detail here.
[0141] Comparative Example 2
[0142] The specific process parameters and performance parameters are detailed in Tables 1 and 2. The others are the same as Example 13 and will not be repeated here.
[0143] 2. Characterization Test
[0144] The relevant parameter testing method in the above embodiment is specifically as follows:
[0145] 1) Active specific surface area of the positive electrode
[0146] The positive electrode sheet was punched into a disc with a diameter of 14 mm, and a button-type half-cell was assembled with a metal lithium sheet as the negative electrode. The positive electrode shell was a CR2023 aluminum-plated shell.
[0147] CV scanning was performed using a constant current scan rate, with scan rates set to 1 mV / s, 0.5 mV / s, 0.3 mV / s, and 0.1 mV / s, respectively. The scan voltage range was 2.8 V to 4.3 V. Four batteries were measured in each group, and four scanned CV graphs were obtained for each battery.
[0148] Superimpose the CV graphs of the four scan rates of each battery, and finally superimpose the CV graphs of the four batteries together. Read the peak current in the CV graph.
[0149] Peak current-square root of scan rate plot: Plot the CV peak current of the four batteries against the square root of the scan rate to obtain four slopes.
[0150] Active surface area calculation: According to the Randles-Sevcik equation: The slope can be used to estimate the active effective surface area on each buckle electrode.
[0151] Calculation of active specific surface area: The mass of the active material on the positive electrode sheet can be calculated based on the active material ratio of each positive electrode sheet and the weight of the positive electrode film layer minus the weight of the current collector. The active specific surface area of the positive electrode sheet can be calculated by dividing the calculated active effective surface area by the mass.
[0152] 2) Morphology test of positive electrode active materials
[0153] The positive electrode active material of the embodiment was tested using a ZEISS sigma 300 scanning electron microscope, and then tested according to the standard JY / T010-1996 to observe the morphology of the sample.
[0154] 3) Test of average particle size and half-peak width of particle size distribution of primary particles
[0155] Software name: LIBMAS Lithium-ion Battery Material Microscopic Intelligent Analysis System. The scanning electron microscope image of the positive electrode active material is used to automatically identify the single crystal particles by LIBMAS Lithium-ion Battery Material Microscopic Intelligent Analysis System. The particle outline, particle quantity, number, area, maximum caliper diameter, average number, distribution map, and manual intervention can be drawn.
[0156] 3.1) Average primary particle size = sum of all measured particle sizes / sum of all measured particle numbers.
[0157] 3.2) Half-peak width of primary particle size curve: The above measured data is plotted as a normal distribution graph with different sizes and the proportion of the number of such sizes, and the half-peak width of the curve is measured to represent the width of the primary particle size distribution.
[0158] The primary particle distribution of Example 1 was measured by primary particle test. Figure 5a and Figure 5b As shown, Figure 5a This is a scanning electron microscope image of the positive electrode active material and the particle contour map after automatic artificial intelligence (AI) identification. Figure 5b It is a normal distribution diagram of the particle size of the primary particles of the positive electrode active material.
[0159] 4) Volume average particle size DV50 test
[0160] Equipment model: Malvern 2000 (MasterSizer 2000) laser particle size analyzer, reference standard process: GB / T19077-2016 / ISO 13320:2009, specific test process: take an appropriate amount of the sample to be tested (the sample concentration is guaranteed to be 8%-12% shading), add 20mL of deionized water, and simultaneously ultraviolet for 5min (53KHz / 120W) to ensure that the sample is completely dispersed, and then measure the sample according to GB / T19077-2016 / ISO 13320:2009 standard.
[0161] 5) Electrochemical performance test
[0162] 5.1) Gram capacity test
[0163] The above battery is tested for the charge and discharge capacity C at 2.8-4.35V at 0.1C. 放 , calculate the gram capacity of the positive electrode material based on the weight of the active material in the positive electrode plate of the battery.
[0164] Battery capacity in grams = battery capacity C 放 (mAh) / mass of positive electrode active material (g).
[0165] 5.2) Rate performance test
[0166] The above batteries were tested at 2.8-4.35V, and the cell capacity was tested using 1C and 3C charge and discharge respectively. The 3C capacity / 1C capacity is used to describe the rate performance.
[0167] 5.3) Cyclic performance test
[0168] At 25°C, the battery was charged and discharged at a rate of 1C, and the voltage range was set to 2.8V~4.35V.
[0169] After 500 cycles, the capacity retention rate was tested.
[0170]
[0171]
[0172] In summary, if Figure 4 As shown, the particles of the positive electrode active material obtained in Example 1 of the present application are evenly distributed, the particle size is relatively uniform, and there is no obvious agglomeration. Figure 5a As shown, the particle contour map of the primary particles of the positive electrode active material is drawn by automatic artificial intelligence recognition. The gray base in the figure is the scanning electron microscope image of the actual test of the positive electrode active material particles, and the blue in the figure is the contour of the primary particles drawn by automatic artificial intelligence recognition, which shows that automatic artificial intelligence recognition can almost reflect the contour of the actual primary particles. Figure 5bThe half-peak width of the primary particles obtained in Example 1 of the present application is shown to be 1.71 μm.
[0173] Comparing Examples 1 and 2 with Comparative Example 1, in the process of preparing the positive active material precursor, by controlling the stirring speed, the sizes of the obtained positive active material precursors are different. The greater the stirring speed, the smaller the volume average particle size DV50 of the formed positive active material precursor, and the larger the specific surface area of the positive active material precursor. The positive active material precursor with a large specific surface area has a higher reaction activity and is easy to nucleate. The generated positive active material primary particles are smaller, and the corresponding positive electrode sheet has a large active specific surface area, which is conducive to the deintercalation of lithium ions, so the gram capacity is high and the rate performance is relatively good. The positive active material precursor with large particle size and small specific surface area in Comparative Example 1 has weak reaction activity. During the synthesis of the positive electrode material, the internal crystallinity is insufficient and the gram capacity is reduced. As shown in Comparative Example 1, due to the large active specific surface area of the positive electrode sheet, the contact with the electrolyte increases, the side reaction occurs more aggravated, and the loss of active materials is accelerated, the gram capacity is low, the cycle capacity retention rate deteriorates, and the cycle capacity retention rate is low.
[0174] Comparing Examples 1 and 3, it can be seen that after the lithium salt is switched from lithium hydroxide to lithium carbonate, the average particle size of the primary particles of the positive electrode active material decreases, and the active specific surface area of the positive electrode sheet increases. This is because the decomposition temperature of lithium carbonate is higher than that of lithium hydroxide, and the heat consumed by lithium carbonate is higher than that of lithium hydroxide. Therefore, under the same sintering conditions, the growth rate of the primary particles is lower than that of the positive electrode active material with lithium hydroxide as the lithium source. In addition, carbon dioxide gas is produced when lithium carbonate decomposes, and the carbon dioxide gas adheres to the whiskers of the crystals. The carbon dioxide gas can inhibit the growth of primary particles, making the particle size of the primary particles smaller. Therefore, using lithium hydroxide as a lithium salt can obtain a positive electrode active material with a larger average particle size of primary particles, and the corresponding active specific surface area of the positive electrode sheet is relatively low. The battery capacity retention rate of Example 1 is 96.3%, which is greater than 94.1% of Example 3, indicating that the cycle life of Example 1 is slightly better than that of Example 3.
[0175] Comparing Examples 1 and 4 with Comparative Example 3, it can be seen that as the oxygen content of the annealing treatment decreases, the primary particle distribution width of the positive electrode active material increases, the gram capacity slightly deteriorates, and the cycle performance deteriorates seriously. Due to the decrease in oxygen content, the precursor is not in sufficient contact with oxygen, and the production speed is different, so the primary particle distribution width becomes larger. In addition, when the oxygen content is insufficient, the crystallinity of the positive electrode active material decreases, affecting the performance of the gram capacity. At the same time, the crystallinity is further reduced, which greatly exacerbates the deterioration of the cycle life.
[0176] Comparing Example 1, Examples 5-7 and Comparative Example 4, it can be seen that as the sintering temperature increases, the average particle size of the primary particles of the positive electrode active material gradually increases, and the active specific surface area of the positive electrode sheet gradually decreases. The gram capacity first increases and then decreases with the increase of the sintering temperature. This is because when the sintering temperature is reduced, although the primary particles of the positive electrode active material are small and the active specific surface area of the positive electrode sheet is large, the internal crystallinity is seriously insufficient due to the low temperature, so the gram capacity is low. When the sintering temperature is high, the primary particles increase, the active specific surface area decreases, and the cycle performance is significantly improved.
[0177] By comparing Example 1 and Examples 8-11, it can be seen that based on Example 8 and Example 9, the increase in the amount of binder increases the bonding force between the particles in the positive electrode sheet, the particle distribution becomes more dense, and the proportion of positive electrode active materials decreases slightly, the active specific surface area of the positive electrode sheet decreases, and the corresponding cycle performance is slightly improved. However, due to the increase in the binder that does not conduct electrons, the rate performance will deteriorate. Based on Examples 10-11, the increase in the conductive agent can increase the active specific surface area of the positive electrode sheet, and the rate performance is improved, but the cycle performance deteriorates. This is because the increase in the conductive agent enhances the reaction activity of the positive electrode sheet, which will lead to the acceleration of the side reactions at the interface between the electrolyte and the positive active material, and the simultaneous acceleration of decomposition and consumption. At the same time, the accumulation of electrolyte decomposition products leads to an increase in the electrode surface impedance. Therefore, as the number of cycles increases, the reversible capacity loss of the battery increases.
[0178] The above are only implementation methods of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A positive electrode sheet, characterized in that: The positive electrode plate includes a positive electrode active material, wherein the positive electrode active material includes lithium nickel oxide, and the active specific surface area of the positive electrode plate is greater than or equal to 2 cm 2 / g, and less than or equal to 4cm 2 / g.
2. The positive electrode sheet according to claim 1, characterized in that: The active specific surface area of the positive electrode plate is greater than or equal to 2.5 cm 2 / g, and less than or equal to 3.5cm 2 / g.
3. The positive electrode sheet according to claim 1 or 2, characterized in that: The positive electrode active material includes primary particles. In a scanning electron microscope image of the positive electrode active material, the half-peak width of the particle size distribution of the primary particles of the positive electrode active material is 1.3 μm-2 μm.
4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The positive electrode active material includes primary particles. In a scanning electron microscope image of the positive electrode active material, an average particle size of the primary particles is 1.5 μm-2.5 μm.
5. The positive electrode sheet according to claim 4, characterized in that: The average particle size of the primary particles is 1.5 μm to 1.97 μm.
6. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: The positive electrode active material includes a structural formula of Li a Ni x Co y A z M (1-x-y-z) O2 material, wherein 0.9≤a≤1.1, 0.54≤x≤0.99, 0≤y≤0.2, 0≤z≤0.4; wherein A includes Mn and / or Al, and M includes one or more of V, Co, Mg, Fe, Zr, Y, Nb, Mo, Cr, B, Ti, Nb, and W.
7. The positive electrode sheet according to claim 6, characterized in that: The Li a Ni x Co y A z M (1-x-y-z) In the material of O2, at least part of the M element is doped in the surface layer of the positive electrode active material.
8. The positive electrode sheet according to claim 6 or 7, characterized in that: The positive electrode active material further includes a coating layer, and the coating layer contains one or more of the elements Al, B, Co, Ti, Nb, W, and Zr.
9. The positive electrode sheet according to any one of claims 1 to 8, characterized in that: The crystal form of the positive electrode active material includes single crystal.
10. A method for preparing a positive electrode sheet, characterized in that: The slurry containing the positive electrode active material is coated on the current collector, and after drying, cold pressing and slicing, a positive electrode sheet is formed, and the active specific surface area of the positive electrode sheet is greater than or equal to 2cm 2 / g, and less than or equal to 4cm 2 / g, and the positive electrode active material includes lithium nickel oxide.
11. The method according to claim 10, characterized in that The preparation method of the positive electrode active material comprises: Adding a nickel source to water and an alkaline solution to perform co-precipitation, adjusting the pH to react and forming a positive electrode active material precursor, wherein the volume average particle size DV50 of the positive electrode active material precursor is 2 μm-4 μm; The lithium source and the positive electrode active material precursor are mixed and annealed to form the positive electrode active material.
12. The method according to claim 11, characterized in that The specific surface area of the positive electrode active material precursor is 13 m 2 / g-35m 2 / g.
13. The method according to claim 11 or 12, characterized in that: The atmosphere of the annealing treatment contains oxygen, and the volume percentage of the oxygen accounts for more than 50% of the atmosphere.
14. The method according to any one of claims 11 to 13, characterized in that: The atmosphere of the annealing treatment contains oxygen, and the volume percentage of the oxygen accounts for more than 80% of the atmosphere.
15. The method according to any one of claims 11 to 14, characterized in that: The pH adjustment reaction to form a positive electrode active material precursor comprises: The pH value is adjusted and the reaction is stirred to form a positive electrode active material precursor; wherein the stirring rate is 600 rpm-1000 rpm.
16. The method according to any one of claims 11 to 13, characterized in that: The lithium source and the positive electrode active material precursor are mixed and annealed to form the positive electrode active material, comprising: The lithium source, the positive electrode active material precursor and the M source are mixed, subjected to a first annealing treatment in an atmosphere containing oxygen, and crushed to obtain a first positive electrode active material, wherein the M source includes a compound containing one or more of the elements Al, B, Co, Ti, Nb, W, and Zr.
17. The method according to claim 16, characterized in that The method further comprises: mixing the lithium source, the positive electrode active material precursor and the M source, performing a first annealing treatment in an atmosphere containing oxygen, and crushing the mixture to obtain the first positive electrode active material; The first positive electrode active material is mixed with a coating source and subjected to a second annealing treatment to form a second positive electrode active material. The coating source includes a compound containing one or more of Al, B, Co, Ti, Nb, W, and Zr elements.
18. The method according to claim 16 or 17, characterized in that The temperature of the first annealing treatment is 700° C.-1100° C.; and / or, The crushing includes crushing in a jet mill with a classifying wheel frequency of 40 Hz-60 Hz.
19. A battery, characterized in that: The positive electrode sheet comprises the positive electrode sheet as described in any one of claims 1 to 9, or / and the positive electrode sheet prepared by the method as described in any one of claims 10 to 18.
20. An electrical equipment, characterized in that: Comprising the battery of claim 19.
Citation Information
Patent Citations
Preparation method of spinel type lithium manganate with high crystallinity used in lithium ion battery
CN101807686A
Negative pole piece, test method of active specific surface area of pole piece as well as battery
CN108844878A
High-nickel ternary positive electrode material with high electrical property consistency, preparation method thereof and application thereof
CN109713252A
Positive electrode material and electrochemical device containing same
CN109860546A
Positive electrode material and electrochemical device using positive electrode material
CN109994729A